FENOMENA HEDONISME: KAJIAN TAFSIR DAN HERMENEUTIKA PAUL RICOEUR TERHADAP QS. AL-ISRA' AYAT 27 BAGI GAYA HIDUP MAHASISWA MASA KINI - Muhtarisah, Nabilatul; Anam, Wahidul (University of Islam Malang, 2024)
A lifestyle that tends towards luxury is usually known as a hedonic lifestyle, as explained in surah al-Isra' verse 27 in the Koran. The hedonistic lifestyle in Surah al-Isra' verse 27 is currently popular among generation Z, but is even more clearly visible among today's students. This can be felt when many students do not buy something because they need it, but instead follow trends only to fulfill their lustful desires. Therefore, researchers want to evaluate the issue of the hedonistic lifestyle in the current contemporary era, the research method is using library research, then the data collected is done by analyzing documents. Then in previous research it was more about analysis using descriptive analysis and using the Maudhu'I (thematic) interpretation method. So the results of the research explain several hedonistic attitudes in verses in the Koran, such as the attitude of loving the world and squandering wealth. However, this article is more about analyzing Surah al-Isra' verse 27 according to the interpretation of Al-Azhar's commentary and Paul Ricoeur's Hermeneutics, as well as its relevance to the lifestyle of today's students. So, this article provides in-depth knowledge regarding the relevance of Surah al-Isra' verse 27 for today's students, thereby making students understand that wasteful lifestyles are only due to lustful desires.